Hybrid-integrated devices for mimicking malignant brain tumors (“tumor-on-a-chip”) for in vitro development of targeted drug delivery and personalized therapy approaches - Zimina, Tatiana M.; Sitkov, Nikita O.; Gareev, Kamil G.; Mikhailova, Natalia V.; Combs, Stephanie E.; Shevtsov, Maxim A. (Frontiers in Medicine, 2024)
Acute and requiring attention problem of oncotheranostics is a necessity for the urgent development of operative and precise diagnostics methods, followed by efficient therapy, to significantly reduce disability and mortality of citizens. A perspective way to achieve efficient personalized treatment is to use methods for operative evaluation of the individual drug load, properties of specific tumors and the effectiveness of selected therapy, and other actual features of pathology. Among the vast diversity of tumor types -brain tumors are the most invasive and malignant in humans with poor survival after diagnosis. Among brain tumors glioblastoma shows exceptionally high mortality. More studies are urgently needed to understand the risk factors and improve therapy approaches. One of the actively developing approaches is the tumor-on-a-chip (ToC) concept. This review examines the achievements of recent years in the field of ToC system developments. The basics of microfluidic chips technologies are considered in the context of their applications in solving oncological problems. Then the basic principles of tumors cultivation are considered to evaluate the main challengers in implementation of microfluidic devices, for growing cell cultures and possibilities of their treatment and observation. The main achievements in the culture types diversity approaches and their advantages are being analyzed. The modelling of angiogenesis and blood-brain barrier (BBB) on a chip, being a principally important elements of the life system, were considered in detail. The most interesting examples and achievements in the field of tumor-on-a-chip developments have been presented.Brain tumor; tumor-on-a-chip, blood-brain barrier, organ-on-a-chip, microfluidic devices